For people making books - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2002)
'If education is the road out of poverty, books are the wheels needed for the journey,' said Richard Crabbe, a Ghanaian publisher who chaired the African Publishers Network from 1997 to 2002. The regular flow of information about books, publishing...